2007
DOI: 10.1080/09603120600937856
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring progress of the role of integration of environmental health education with water and sanitation services in changing community behaviours

Abstract: The health benefits of clean water, improved sanitation and better hygiene are now more recognized than ever before. The objective of the present study focused on monitoring the progress of behavioural changes towards appropriate behaviours related to water, environment and sanitation (WES). This was achieved through assessing the baseline community behaviours towards WES, exploring to what extent community hygienic behaviours had changed towards desirable and sustainable behaviours, through monitoring progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…There are several methods for assessing hand washing practice. Self-reported hand washing behavior uses structured or informal interviews to assess an individual's hand washing behavior 28–32. Direct observation of hand washing practices consists of an observer directly observing an individual's hand washing practices 33–36.…”
Section: Methodsmentioning
confidence: 99%
“…There are several methods for assessing hand washing practice. Self-reported hand washing behavior uses structured or informal interviews to assess an individual's hand washing behavior 28–32. Direct observation of hand washing practices consists of an observer directly observing an individual's hand washing practices 33–36.…”
Section: Methodsmentioning
confidence: 99%
“…Curtis’s intervention (2001), which was based on formative research of childhood diarrhoeal disease, was followed by structured observations of young children and their caretakers. Metwally’s observation (2007) of handwashing practices followed the launch of a water, environment and sanitation community promotion within four Egyptian districts. His method included monitoring the progress of communities’ behaviour change over a 3‐year period.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Pakistan found that 38% expressed a refusal to donate (14). Many interventional studies for behavioral changes that were done in Egypt provided concrete results about the marvelous effect and influence of creating awareness among communities especially rural and closed ones for improving healthy behaviors for different health care aspects (15)(16)(17)(18)(19), so creating awareness is a key entry among Egyptians to raise their acceptance to donate after death.…”
Section: Discussionmentioning
confidence: 99%